Material Planning with ABC Classification, Min-Max Method, and Continuous Review System Method at PT XYZ - Wardana, Farhan Jezando; Zamzani, Muhammad Imron; Purba, Arini Anestesia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is a petrochemical manufacturing company that produces industrial raw materials. This company has a stock of inventory materials in its warehouse. The background of this research is based on the company's need to optimize raw material inventory management to ensure the smooth running of the methanol production process and prevent overstock and stock of material. This study analyzed company SAP data, which showed a high average overstock level in CR1-B2-C01 storage during 2018-2022. Forty materials were overstocked, and 22 materials were out of stock. This shows the urgency to classify priority inventory materials, determine the research results in minimum and maximum quantities of materials, and determine reorder points. The research methods used include the ABC classification to classify inventory priorities, the Min-Max method to calculate the minimum and maximum amount of material, and the Continuous Review System method to determine reorder points and the amount of inventory to be provided. Data on purchases and usage of Parker O-Lube and O-Ring Parker materials in CR1-B2-C01 storage during 2018-2022 are used as a basis for planning material requirements. The research results found that by applying the ABC classification, the Min-Max method, and the Continuous Review System method, the company can optimize the management of CR1-B2-C01 raw materials. In investing in raw materials, companies can reduce the risk of unnecessary costs, minimize damage to goods, and prioritize the optimal use of storage space.